Energy Expenditure, Lipid Profile, Oxidative Stress, and Cardiac Energy Metabolism After Growth Hormone Treatment in Obese Young Rats - Seiva, F. R. F. [UNESP]; Berbert, C. M. S. [UNESP]; Souza, G. A. [UNESP]; Rocha, K. K. H. [UNESP]; Ebaid, Geovana Xavier [UNESP]; Burneiko, R. C. M. [UNESP]; Novelli, E. L. B. [UNESP] (Georg Thieme Verlag Kg, 2010)
Obesity is rampant in modern society and growth hormone (GH) could be useful as adjunct therapy to reduce the obesity-induced cardiovascular damage. To investigate GH effects on obesity, initially 32 male Wistar rats were divided into two groups (n = 16): control (C) was fed standard-chow and water and hyper-caloric (H) was fed hypercaloric chow and 30% sucrose in its drinking water. After 45 days, both C and H groups were divided into two subgroups (n = 8): C + PL was fed standard-chow, water and received saline subcutaneously; C + GH was fed standard-chow, water, and received 2 mg/kg/day GH subcutaneously; H + PL was fed hypercaloric diet, 30% sucrose in its drinking water, and received saline subcutaneously; and H + GH was fed hypercaloric diet, 30% sucrose in its drinking water, and received GH subcutaneously. After 75 days of total experimental period, H + PL rats were considered obese, having higher body weight, body mass index, Lee-index, and atherogenic index (AI) compared to C + PL. Obesity was accompanied by enhanced myocardial lipid hydroperoxide (LH) and lactate dehydrogenase (LDH), as well of depressed energy expenditure (RMR) and oxygen consumption(VO(2))/body weight. H + GH rats had higher fasting RMR, as well as lower AI and myocardial LH than H + PL. Comparing C + GH with C + PL, despite no effects on morphometric parameters, lipid profile, myocardial LH, and LDH activity, GH enhanced fed RMR and myocardial pyruvate dehydrogenase. In conclusion, the present study brought new insights into the GH effects on obesity related cardiovascular damage demonstrating, for the first time, that GH regulated cardiac metabolic pathways, enhanced energy expenditure and improved the lipid profile in obesity condition. Growth hormone in standard fed condition also offered promising therapeutic value enhancing pyruvate-dehydrogenase activity and glucose oxidation in cardiac tissue, thus optimizing myocardial energy metabolism.
Keywords: growth hormone; calorimetry; lipid profile; heart; energy metabolism; oxidative stress